Culture and Human Action as Forces of Environmental Problems in Chinua Achebe’s Things Fall Apart - Nwoma, Chukwu Romanus (American Journal of Humanities and Social Sciences, 2018)
Chinua Achebe’s Things Fall Apart has been subjected to different critical and theoretical orientations that have examined and reexamined the novel within the context of various existential realities but this study is an eco-critical reading of the novel. Ecocriticism is not only the study of the environment in literature as the environment has been an issue in literary studies. It is rather a radical approach to rethinking the relationship between humans and the environment; a proponent of ethical human-environmental interactions. Through the eco-critical methodical approach, the study interrogates and reveals the cultural orientations that induce environmental mistreatment by the characters in the novel under study. Environmental problems in the novel are revealed both as implacable forces and uncanny reactions. The discovery is that the characters subdue the environment with various socio-economic activities as the environment consequently reacts to the actions of the characters. The patterns of oppression and subjugation of the environment are revealed as the characters are considered responsible for the environmental problems that threaten their existence. The study advances the process of rethinking literature and criticism as it also advances the frontiers of the emerging discipline of environmental humanities.